Моделювання реклами нового споживчого товару довгострокового використання - Заруба, Віктор Яковлевич; Парфентенко, Ірина Анатоліївна (НТУ "ХПІ", 2018)
Розглянуто моделі дослідження ефективності реклами, які дозволяють оптимізувати рекламні витрати. Обґрунтовано доцільність використання для розробки цих моделей методу послідовного взаємозв’язку показників комунікаційної та економічної ефективності. Відмічені переваги динамічних моделей мають у порівнянні із статичними. За методом послідовного взаємозв’язку розроблена і досліджена динамічна модель рекламування у засобі масової інформації нового споживчого товару довгострокового використання. За критерієм максимального економічного ефекту визначені оптимальні величини загальної кількості рекламних звернень та витрат на рекламу за час її проведення.

The models of investigation of advertising effectiveness, which allow to optimize advertising costs, are considered. The expediency of using the method of consistent correlation of indicators of communication and economic efficiency for the development of these models is substantiated. In accordance with this method, it is necessary to trace the links of the final goal of advertising with intermediate goals and, as a result, with the advertising budget. It is shown that dynamic models have advantages in comparison with static ones. They are able not only to describe advertising as changes that occur over time, but also more accurately determine the dependencies between the input and output parameters of static models. In accordance with the method of consistent interrelation, a dynamic model of advertising a new consumer product for long-term use in the media has been developed and investigated. The optimal values of the number of advertising appeals and advertising costs, which provide the maximum economic effect, are determined.
Modeling advertising the new consumer durable goods
Keywords: ефективність реклами; рекламні витрати; рекламні звернення; динамічна модель рекламування; модель Літтла; advertising effectiveness; advertising costs; advertising appeals